Factors Influencing Federal and State Probation Officer Turnover Intention. Issue 4 (1st October 2016) - Blankenship, Chastity; Slate, Risdon N.
ABSTRACT: Stress among criminal justice professionals is generally associated with turnover intention. This study uses survey data from over 700 state and federal probation officers from the same southern jurisdiction to explore factors significantly related to turnover intention. Pearson correlation and a structural model reveal significant relationships between a variety of variables such as the agency where a probation officer works, perceptions of participation in workplace decision making, job satisfaction, and physical stress as predictors of turnover intention. The results support the importance of job satisfaction, participatory management, positive work environment and physical stress as factors related to turnover intention.